Chromatin architecture and nuclear RNA. - Nickerson, J A (1989)
The maintenance of normal chromatin morphology requires ongoing RNA synthesis. We have examined the role of RNA in chromatin organization, using selective detergent extraction of cells, RNA synthesis inhibitors, and enzymatic digestion of nuclear RNA. Comparison of extracted and unextracted cells showed that the important features of chromatin architecture were largely unchanged by the extraction procedure. Normally, chromatin was distributed in small heterochromatic regions and dispersed euchromatic strands. Ribonucleoprotein granules were dispersed throughout the euchromatic regions. Exposure to actinomycin led to the redistribution of chromatin into large clumps, leaving large empty spaces and a dense clustering of the remaining ribonucleoprotein granules. When the nuclei of extracted cells were digested with RNase A, there was a rearrangement of chromatin similar to but more pronounced than that seen in cells exposed to actinomycin. The inhibitor 5,6-dichloro-1-beta-D-ribofuranosylbenzimidizole also inhibits RNA synthesis but by a different mechanism that leaves no nascent RNA chains. The drug had little effect on chromatin after brief exposure but resembled actinomycin in its effect at longer times. We also examined the structure of the nuclear matrix to which most heteronuclear RNA remains associated. Pretreatment of cells with actinomycin or digestion of the nuclear matrix with RNase A caused the matrix fibers to collapse and aggregate. The experiments show a parallel decay of chromatin and of nuclear matrix organization with the depletion of nuclear RNA and suggest that RNA is a structural component of the nuclear matrix, which in turn may organize the higher order structure of chromatin.